THE DETERMINANTS OF CASH HOLDING - Susanti, Merry; Susanto , Liana (International Journal of Application on Economics and Business, 2024)
The aim of this research was to empirically prove the influence of profitability, leverage, sales growth, and capital expenditure on cash holding. The sample selection method used purposive sampling. The research sample was 63 primary consumer sector companies listed on the Indonesia Stock Exchange with a research period of three years and were processed by multiple regression analysis of panel data using the Eviews. The research results showed that there was only one variable, namely leverage, which had a negative impact on cash holding. Profitability did not have a positive impact on cash holding, while sales growth and capital expenditure did not have a negative impact on cash holding.